THE THEORETICAL ASPECT OF DELPHI TECHNIQUES AND AHP METHOD - RAMAJ-DESKU, Behrije; BERISHA, Vlora; LATIFI, Thelleza; LOKA, Alma (Theoretical and Practical Research in Economic Fields; Vol 11 No 1 (2020): TPREF, Volume XI, Issue 1(21), Summer 2020, 2020)
Various researchers in Iran, Germany, Central Taiwan, Brazil and U.S have selected to apply the combined Delphi technique and AHP method in their studies. These two techniques have been used to rank and identify factors, elements, importance measurement, expert perceptions of a topic, etc. The areas where these studies, and we are based on our analysis, are tourism industry and beverage industry but the focus falls on marketing, social media, content marketing, e-commerce and e-business. The general purpose of this paper is to address in general terms the Delphi technique and AHP method.